Teachers’ Perspectives on the Contribution of Social Studies Education to the Formation of Students’ Social and Cultural Identity through a Deep Learning Approach - Aliem Sayyidah; Abdul Asrori; Ajar Dirgantoro; Sulastri Rini Rindrayani (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
Education plays an important role in shaping students’ social and cultural identity, particularly through Social Studies learning at the junior secondary level. However, Social Studies instruction is often still oriented toward cognitive achievement and lacks contextual learning experiences, which limits the internalization of social and cultural values in the midst of globalization and the gradual erosion of local culture. Therefore, this study aims to examine teachers’ perspectives on the contribution of Social Studies learning through a deep learning approach to the formation of students’ social and cultural identity in Pacitan Regency. This study employed a descriptive qualitative approach with a case study design. The participants consisted of 5–10 junior secondary Social Studies teachers selected purposively. Data were collected through semi-structured interviews, classroom observations, and document analysis. The data were analyzed using thematic analysis techniques, including data reduction, data display, and conclusion drawing. The validity of the data was ensured through source triangulation, technique triangulation, and member checking. The findings indicate that teachers perceive Social Studies learning as having a strategic role in fostering students’ social and cultural identity through the internalization of social, cultural, national, and civic values. The implementation of a contextual deep learning approach supports students’ understanding, reflection, and meaning-making processes in relation to their social and cultural environment. However, the implementation still faces several challenges, including limited instructional time, resource constraints, and variations in teacher readiness.